Characterisation of sheep and goat genetic resources in their production system context in northern Kenya - Warui, H.M. (University of Hohenheim, 2008)
Approximately 25 % of the world’s land surface support about 20 million households or about 180–200 million people in pastoral areas (Degen, 2007). Pastoral production systems are low external input systems that Kaufmann (2007) characterizes as probabilistic rather than deterministic, since outcome in such systems resulting from the inputs cannot be predicted with certainty. Although this applies to other agricultural systems as well, in pastoral systems the degree of uncertainty is higher particularly due to high temporal and spatial variability of resource availability. Moreover, several disturbance factors affect livestock production in the pastoral areas in the Sub-Saharan Africa. These include recurrent droughts, uncontrolled livestock diseases, inter-tribal conflicts and animal raids. Pastoralists also receive few extension including veterinary services and have inadequate market access due to poor infrastructure (roads and telecommunication services). The pastoralists rely on their local knowledge to manage their animal genetic resources (AnGR). However, according to Wilson (2007) even though local knowledge is crucial for survival of the poor people, being agents of their own development is not enough. Moreover, pastoralists require external support in overcoming the impact of the extreme conditions of the disturbance factors like drought, diseases and conflicts. Pastoralists can cope with the disturbance factors when they are not extreme. Pastoralists keep local breeds of camels, cattle, sheep, goats and donkeys that they largely depend on for their livelihood. Local breed is a livestock population in which livestock keepers ascribe member animals. The term "local" also denotes a breed’s adaptation to the prevailing production conditions (Kaufmann, 2007). The local breeds are multi-functional in the pastoral production systems in Sub-Saharan Africa. They serve at meeting pastoralists’ socio-cultural, subsistence and economic needs. The high proportion of small ruminants in pastoral production systems in Africa attests their importance in pastoral areas. Lebbie and Ramsay (1999), for example, reported that sheep and goats constitute 28% and 34% of the total domesticated ruminant livestock in the Sub-Saharan Africa. Out of these 57% and 64% respectively, are found in the arid and semi-arid lands. Due to the short generation interval and high reproductive rate, sheep and goats are especially relied on when rebuilding herds after extreme droughts or animal raids. After the impact of these disturbance factors, small ruminants are exchanged with the large ruminants within the community or sold to outside market to buy the large ruminants. It is widely recognized that local breeds of sheep and goats that have evolved under the harsh conditions in pastoral systems are well adapted to those conditions (Rege, 1992, Degen, 2007). The performance of the local breeds should therefore be assessed in their production context and not compared with exotic breeds out of this context. The relevance of the local breeds’ traits is specific to their production system context. Characterisation of livestock resources in their production system context entails identifying traits that are of interest to the livestock keepers, be it with regard to maintenance and reproduction of the herd, to utilisation of the livestock and their products and to livestock breeding. The livestock resources possess traits and show trait INTRODUCTION 2 levels that enable them to fulfill the respective functions. The livestock keepers’ management influences the trait levels (K aufmann, 2007). In this respect, the approach of characterizing animal resources in their production system context is an actor- oriented approach. In the present study, sheep and goats genetic resources of the Gabra and Rendille livestock keepers were characterized in their production system context in Marsabit district, Northern Kenya. The main objectives of the study were: 1. To determine the functions of sheep and goats within the pastoral production system context in Marsabit District. 2. To exemplarily identify the management practices of sheep and goats. 3. To determine traits of sheep and goat populations that are relevant to the livestock keepers. 4. To quantitatively assess trait levels of relevant traits at population level in order to characterize the goat resources. The study includes 6 major chapters. Following the current chapter, is the literature review. It covers pastoral production systems, local knowledge of pastoralists, small ruminant genetic resources, and characterisation of animal genetic resources. Chapter 3, deals with the materials and methods. The study area is first described. This is in terms of bioclimatic conditions, livestock, human demography, infrustructure and extension services. Also explained is the study design, theoretical model and data collection using both qualitative and quantitative research methods. Data management and analysis, which entailed qualitative and quantitative procedures, are also given. The results are presented in chapter 4. With regard to Gabra and Rendille sheep and goats, the results are given on age and sex classes, functions, management, relevant traits and preferred levels and animal types. Results on performance of goats are also presented, with regard to body condition of does, reproduction performance and milk yield. Chapter 5 deals with the discussion. It first covers characterisation and management of sheep and goats by Gabra and Rendille pastoralists. Secondly, performance of goat genetic resources under pastoral management of Gabra an d Rendille pastoralists. Thirdly, productive adaptability and drought tolerance in the small ruminants. Fourthly, methodology for characterisation of animal genetic resources in their production system context. Summary of the whole study is given in chapter 6.